11 Monocyte activation & novel biomarker sub-study of LoDoCo-MI. (16th October 2019) - Hennessy, T; Matthews, V; Kurup, R; Rudnicka, C; Schlaich, M; Patel, S; Hillis, G
Abstract : Introduction: Inflammatory monocytes, in particular intermediate and non-classical sub-types play a central role in triggering an acute MI with activation of such monocytes implicated in recurrent events. We hypothesize that treatment with low-dose colchicine may reduce recurrent cardiovascular events by suppression of monocyte activation in patients following an acute MI. The benefits of colchicine in atherosclerosis are mediated by suppression of inflammasome activation (particularly NLRP3) thereby reducing the release of pro-inflammatory cytokines in particularly Interleukin1β(IL) and IL-18. A reduction in NLRP3 activation is reflected in an overall reduction in monocyte activation and monocyte-platelet aggregation. Monocytes are defined by CD14 and CD16 expression. CD16+ monocytes are inflammatory; intermediate and non-classical. Aims: The specific aims of this mechanistic sub-study are to explore the markers of monocyte activation by FC and novel cytokine biomarkers(IL)in survivors of acute MI at 30 days. Hypothesis: We hypothesize that treatment with low-dose colchicine will attenuate monocyte activation and novel cytokine biomarkers following acute MI and that this may be a potential mechanism whereby colchicine treatment can reduce recurrent major adverse clinical events (MACE) in this setting. This mechanistic pilot study will test this hypothesis. Methods: We assessed monocyte activation by performing flow cytometry on fresh blood samples from patients recruited into the LoDoCo-MI study (Randomised Placebo controlled). Specimens were analysed at baseline (within 7 days of the index MI) and at 30 days using a panel of monocyte activation biomarkers table 2). This randomized placebo-controlled sub-study recruited patients following an acute MI and randomized patients 1:1 to colchicine 0.5 mg once daily or matching placebo for 30-days. ELISA was performed for cytokines/biomarkers on bio banked specimens including IL-1β(n=193), IL-6(n=199) and MPO(n=200) in addition to the hs-CRP (the primary biomarker in the primary LoDoCo-MI study) from a portion of the LoDoCo-MI cohort (figure 1 ) Flow cytometry sub-analysis of 6 patients at baseline and 30 days post-treatment.1)CD14+/MAN1+ (activated monocytes or macrophages) 2)CD14-/CD41+ (platelets) 3)CD14-/CD16+ (NK cells, neutrophils or T cells) 4)CD14-/CD61+ normal and activated platelets). Results: No significant difference between the treatment and control arm for interleukin(IL)cytokine biomarkers IL 1B, IL-6, MPO (table 1). On FC, the non-classical inflammatory monocyte CD16+ was markedly elevated (versus classical monocytes CD14-) in all acute MI patients(n=6) with abrupt suppression following treatment. The platelet%(CD41+ and CD61+) appear to always be lower after treatment initiation (figure 1 ). The CD61+ results are variable after treatment. Conclusion: A 'biologically plausible' elevation in CD14+ and CD16+ inflammatory 'non-classical' monocytes was observed immediately after acute coronary syndrome and a sharp drop with treatment. Study numbers in this mechanistic biomarker sub-study were too small and likely under-powered to reveal any significant trend(between colchicine and placebo arms) in contrast to the main study which showed a strong trend in hs-CRP attenuation with colchicine. It offers pilot data to help design a larger scale future study and is thus hypothesis-generating. The consistent flare in non-classical inflammatory monocytes is consistent with prior data.